Techno-Economic Analysis of Municipal Solid Waste Gasification for Electricity Generation - Eliasu, Ali; Derkyi, Nana Sarfo Agyemang; Gyamfi, Samuel (International Journal of Energy Economics and Policy, 2022)
Due to an overburdened national grid, chronic energy challenges, and the growing municipal solid waste menace, a unique opportunity to deploy waste-to-energy technology in Ghana is apparent. A techno-economic analysis was performed for meeting the primary electrical load of selected blocks at the University of Energy and Natural Resources through Municipal Solid Waste gasification. Three scenarios were simulated and assessed based on their Net Present Costs (NPC) and Levelised Cost of Energy (LCOE): a gasifier-standalone system, a grid-tied gasifier system and a grid-alone system. The grid-tied gasifier system was found to meet the 230.1kWh/day electrical load at the least NPC ($2, 049790.00) and COE ($0.09426/kWh). The sensitivity analysis showed that the load factor, sell-back price of electricity and cost/ton of MSW had the most impact on the NPC of the gasification system. MSW gasification is, therefore, an economically viable alternative if grid-integrated. Finally, the study showed that Feed-in Tariffs, plant siting and demand response strategies are crucial to ensuring the cost-effectiveness of gasification systems.